Investigating stress, anxiety, and coping strategies among higher education students in extreme contexts: insights from Romania during the COVID-19 pandemic - Simionescu, Mihaela; Mahmoud, Ali B; Strielkowski, Wadim; Jula, Nicolae-Marius (BMC public health, 2024)
BACKGROUND: Using the perspective of the recent COVID-19 pandemic, which represents a public health challenge that also affects education and the psychological well-being of students, this paper aims to assess the vulnerability to anxiety and stress of the Romanian students from the Faculty of Administration and Business of the University of Bucharest pursuing their degrees in administration and business. METHODS: Our study is based on the results of the survey that was administered to a sample of 422 students (39.6% females and 60.4% males) selected from the pool of 2000 recruited respondents. We employed the ANOVA/linear Dependent Dirichlet Process mixture model to explain the causes of stress and anxiety after various grouping variables represented by gender, specialisation, as well as labour market status. RESULTS: Our results revealed that more than 80% of the students in the sample yielded medium and high vulnerability to stress, while 64% of the respondents were affected by severe anxiety (high frequency of psychological, social, and physical problems that were difficult for them to control). The most important stressors were the fear of getting infected and social distancing, while self-control was considered the most effective coping strategy by 62.6% of employed students. CONCLUSIONS: These results allow us to provide practical recommendations for effectively coping with stress and anxiety among students in Romania and beyond and to help stakeholders and policymakers design strategies for strengthening students' resilience, mental health, and well-being in case of future pandemics or other extreme contexts.
Keywords: COVID-19 pandemic; Extreme contexts; Rumunsko; Pandemics; psychický stres; adaptace psychologická; SARS-CoV-2; Universities; průzkumy a dotazníky; mužské pohlaví; studenti; COVID-19; Adult; mladý dospělý; Stress, Psychological; univerzity; Romania; Young Adult; ženské pohlaví; copingové dovednosti; Humans; Adaptation, Psychological; úzkost; Students; Surveys and Questionnaires; Anxiety; Coping Skills; dospělí; Stress; pandemie; Female; Higher education; lidé; Male